Geological and Geophysical Study in Udheri Khola Area, Nalgad Hydroelectric Project, Jajarkot District, Lesser Himalaya, Western Nepal - Lamsal, Indra; Ghimire, Subesh; Acharya, Kamala Kant (Bulletin of the Department of Geology, 2020)
Subsidence in carbonate rock is one of common and challenging action in terms of engineering construction. Geological study and geophysical investigation carried out in the intake area of Nalgad Hydroelectric Project Jajarkot, western Nepal Lesser Himalaya. The main objective was to identify the cause of subsidence in the intake area of Nalgad Hydroelectric Project, Jajarkot. Geological study of the area was carried to understand the lithology, thickness and structure of the area. The study area comprises two distinct rock units, namely, Dolomite Unit followed up by the Slate Unit. The Dolomite Unit is composed of light grey to grayish white stromatolitic dolomite which is thrusted over the Slate Unit near to Laikham village and Sepu Khola area. The Slate Unit is made up of grayish black to graphitic slate. A thin prominent calcareous horizon wasconfined between Slate Unit. 2D-Electric Resistivity Tomography (ERT) measurements were deployed in four different lines to investigate the cause of the subsidence in the carbonate terrain. A concentric very high resistivity patch shown by Tomogram ER-D-01 survey line was identified and interpreted as dry cavity. The result of the 2D- ERT survey was correlated with core log data of geotechnical exploration in the suspicious point to ensure the presence of karst in the Dolomite Unit at right bank of Nalsyagu Khola near dam axis of Nalgad Hydroelectric Project. The 2D – ERT survey together with geotechnical investigation is capable of identifying subsurface karst feature as the cause of surface collapse in the area.